Development of a Learners’ Dictionary of Polysemous Japanese Words and Some Proposals for Learners’ Lexicography - Shingo IMAI (Acta Linguistica Asiatica, 2012)
The dictionary series Nihongo tagigo gakushū jiten (“A Learner’s Dictionary of Multi-sense Japanese Words”) proposes a new approach to learners’ dictionaries, based on cognitive linguistics theory and on a corpus-based approach. Each entry is presented as a semantic network which follows the patterns of semantic extensions from a word's core meaning to derived meanings. A corpus, Sketch Engine, was consulted in order to select natural and frequently used examples, which were then edited to make them understandable to learners. Illustrations are also provided in an attempt to visualise the common meaning (schema) shared by the various meanings of the word.